Sipping Soft Power : Coffee as Indonesia's Nation Branding Strategy in the US - Joaena Charlotte Rosevine Wattimena; Indra Wisnu Wibisono; Roberto OC Seba (Badan Penerbit STIEPARI Press, 2024)
“Sipping soft power” describes how simple activities such as brewing and enjoying coffee can be a subtle way to convey cultural values, strengthen international relations, and build a positive image of Indonesia in the eyes of the world. In the context of bilateral relations that have been established for over 75 years, coffee has transformed into a cultural symbol reflecting Indonesia's national identity. Using a qualitative case study approach with Nation Branding theory (Anholt) and soft power theory (Nye), this study utilizes data from official reports, scientific literature, and documentation of coffee diplomacy activities. The research findings indicate that the diversity of coffee flavors from various regions in Indonesia, born from tropical geographical conditions, fertile volcanic soil, and sustainable agricultural practices, makes coffee a representation of Indonesia's cultural and natural wealth. Coffee-drinking traditions such as tubruk coffee and klotok coffee are part of social life and offer authentic narratives that strengthen Indonesia's cultural appeal in the eyes of the American public. Through active promotion involving businesses, the diaspora, and state diplomacy, coffee has successfully created cross-cultural emotional experiences that bring foreign consumers closer to Indonesia's local values. This makes coffee not only an economic commodity but also a symbol of national identity that strengthens Indonesia's positive image in bilateral relations with the United States.